دراسة مقارنة للخصائص السيكومترية والبنية العاملية لمقياس الذكاء العاطفي لسكوت في نسخته الأولى والمطورة - نصرات, السعيد (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: هدفت هذه الدراسة لفحص الخصائص السيكومترية (الصدق والثبات) والبنية العاملية لمقياس الذكاء العاطفي في صورتيه الأولية لسكوت وآخرون (1998)Schutte et al. ، والمطورة لأستون وآخرون (2004) et al. Astonوالمكيف على البيئة العربية من قبل نبيل محمد زايد (2009) لدى تلاميذ المرحلة الثانوية بولاية الوادي. وللتحقق من فرضيات الدراسة استخدم الباحث المنهج الوصفي بأسلوبيه التحليلي والسببي المقارن، وقد تم اختيار عينة التقنين عشوائيا للنسخة الأولية (293)، والمطورة (295) من عينتين أساسيتين على التوالي (700) و(706). وبعد تطبيق المقياسين على أفراد عينتي التقنين أظهرت النتائج التالية: -تأكدت دلالات صدق المقياسين بطرق مختلفة (صدق الاتساق الداخلي، الصدق المرتبط بالمحك، وصدق المفهوم)، وكانت الأفضلية لمقياس سكوت وآخرون (1998) في الخصائص السيكومترية، وللنسخة المطورة (2004) في البنية العاملية، بعد تعديل بعض فقراته. - تأكدت دلالات ثبات المقياسين بطرق مختلفة (ألفا كرونباخ للنسخة الأولية، وألفا الطبقية للنسخة المطورة، والثبات بالإعادة، ومعامل الثبات المركب (CR). The present study aimed to examine the psychometric properties (validity and reliability) and the factor structure of the emotional intelligence scale in its primary form of Scott et al (1998), and the expanded one of Aston et al (2004), adapted by Nabil Mohamed Zayed (2009) on the Arab environment among secondary school students in the Willaya of El-Oued. In order to verify the hypotheses of the study, the researcher used the descriptive analytical method, and the rationing sample was randomly selected for the initial version (293) and the developed one (295) from the two main samples of study, respectively (700) and (706). After applying the two scales to the two ration samples, we arrived at the following results: - The indications of validity of the two scales were confirmed in different ways (internal consistency validity, validity of the criteria and construct validity), and preference was given to the scale of Scott et all. (1998) in psychometric properties, and to the developed version (2004) in the factorial structure, after modifying some of its paragraphs. - The stability of the two scales was confirmed by different methods (Cronbach's alpha for the initial version, stratified alpha for the developed version, and test-retest reliability, Composite reliability).
دراسة وصفية على عينة من تلاميذ الطور الثانوي بولاية الوادي
أطروحة دكتوراه تخصص القياس والتقويم في العلوم الانسانية و الاجتماعية
Keywords: الذكاء العاطفي، الخصائص السيكومترية، البنية العاملية.; Electron collision ionization, ionization effective sections, ionization rate, FAC program, electron energy distribution functions